2017
DOI: 10.3389/fpls.2017.01340
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Reagents Involved in Grape Bud Break and Their Effects on Different Metabolites and Related Gene Expression during Winter

Abstract: To elucidate promoting and inhibiting effects of hydrogen cynamide (HC) and abscisic acid (ABA) on quiescence release of grape buds, physiological and molecular approaches were used to explore the mechanisms of quiescence based on metabolic and gene expression analysis. Physiological and molecular mechanisms involved in bud quiescence of grape were studied before and after application of HC, ABA, and ABA-HC. The data showed that ABA inhibited proclamation of quiescence in grape buds and attenuated the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…In many cases, the determination of dormancy or sprouting mainly depends on the balance between ABA and GA levels. HC treatment leads to a decrease in the endogenous ABA level by promoting ABA degradation and inhibiting ABA synthesis, as shown in grape [11] and sweet cherry [6]. In this study, ABA concentration decreased gradually with bud breaking in the HC treatment group (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In many cases, the determination of dormancy or sprouting mainly depends on the balance between ABA and GA levels. HC treatment leads to a decrease in the endogenous ABA level by promoting ABA degradation and inhibiting ABA synthesis, as shown in grape [11] and sweet cherry [6]. In this study, ABA concentration decreased gradually with bud breaking in the HC treatment group (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Many experiments have shown that H 2 O 2 content increases in buds with HC treatment [4, 6, 11], which is the major factor responsible for bud break. H 2 O 2 treatment inhibits CAT activity, which then generates respiratory stress, leading to cell hypoxia and anaerobic respiration [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bud dormancy mechanisms in perennial fruits has been previously explored at the molecular level using omics-based approaches [3,5,25,26]. However, the effect of HC in the release of grape dormancy by coupling transcriptomic and proteomic approaches has not been yet investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Against a background of a growing number of extensive molecular and biochemical studies of the later stages of bud development in grapevine (Halaly et al, 2008; Ophir et al, 2009; Meitha et al, 2015; Zheng et al, 2015; Sudawan et al, 2016; Khalil-Ur-Rehman et al, 2017; Meitha et al, 2017; Signorelli et al, 2018; Zheng et al, 2018a), few have followed development for an extended period of time, from the onset of dormancy. The most extensive catalogue to date spanned the transcriptional state of the bud from shoot development, prior to the summer solstice and periderm formation, through to bud burst following winter (cv.…”
Section: Introductionmentioning
confidence: 99%